A review of the melliferous flora of Yucatan peninsula, Mexico, on the basis for the honey production cycle - Donají Zúñiga-Díaz; William Cetzal-Ix; Héctor López-Castilla; Eliana Noguera-Savelli; Iván Tamayo-Cen; Jesús Froylán Martínez-Puc; Saikat Kumar Basu (BMC, 2024)
Abstract Background The Yucatan Peninsula (YP) is one of the most important regions in global apiculture. Hence, this work reviews and integrates the knowledge of the species diversity, growth habits, ecosystems, floral calendars during the apiculture production cycles and the types of vegetation represented in the melliferous flora (MF) of the YP; as a basis for proposing selection strategies locating suitable apiculture production areas for local beekeepers and help in the economic development of the region. Methods A comprehensive review of the MF literature was carried out using the snowball method to determine and update the number of species useful for apiculture. The growth habits and flower calendars were determined through a review of the literature and databases of specimens from the herbaria CICY, UCAM and MEXU. Results The YP reports a total of 935 taxa of MF (98 families and 498 genera); of these, Campeche has 812 taxa, followed by Quintana Roo (786) and Yucatán (767). The MF is made up of herbs (282), followed by shrubs (260), trees (229), climbers (82), woody climbers (67) palms (14) and parasitic plant (1). Conclusion Of the 935 species of MF registered at the regional level, a high number of species have flowering throughout the year, however, not all of these species are considered useful for local commercial apiculture. Only a select group of 23 species are considered of major importance for local apiculture industry.